2014
DOI: 10.1016/j.pbb.2013.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of OPRM1

Abstract: Pharmacogenetic research has the potential to explain the variation in treatment efficacy within patient populations. Understanding the interaction between genetic variation and medications may provide a method for matching patients to the most effective therapeutic options and improving overall patient outcomes. The OPRM1 gene has been a target of interest in a large number of pharmacogenetic studies due to its genetic and structural variation, as well as the role of opioid receptors in a variety of disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 116 publications
1
74
0
1
Order By: Relevance
“…OPRM1, the gene encoding the m-opioid receptor, is associated with nicotine dependence, tobacco smoking and smoking initiation [110,111]. Furthermore, genetic variation in OPRM1 may affect susceptibility to opioid dependence.…”
Section: Pharmacogenetic Interactions With Nicotine and Opioidsmentioning
confidence: 99%
“…OPRM1, the gene encoding the m-opioid receptor, is associated with nicotine dependence, tobacco smoking and smoking initiation [110,111]. Furthermore, genetic variation in OPRM1 may affect susceptibility to opioid dependence.…”
Section: Pharmacogenetic Interactions With Nicotine and Opioidsmentioning
confidence: 99%
“…Similarly, analyses of alcohol dependence have reported increased risk (Bart et al 2005; Kim et al 2004), no effect (Bergen et al 1997; Rouvinen-Lagerstrom et al 2013; Sander et al 1998; Xuei et al 2007), and decreased risk (Schinka et al 2002; Town et al 1999) for this allele. Analyses of rs1799971 with other addictive substances also show no consensus (Clarke et al 2013; Crist and Berrettini 2013; Franke et al 2001; Gelernter et al 1999; Hardin et al 2009; Munafo et al 2013). …”
Section: Introductionmentioning
confidence: 98%
“…However, the role, if any, of rs1799971 in substance dependence remains unclear (Crist and Berrettini 2013; Levran et al 2012; Mague and Blendy 2010). In studies of opioid dependence, results have been mixed, with the minor (G) allele reported to have no effect in some studies (Crowley et al 2003; Levran et al 2008; Nelson et al 2014; Nikolov et al 2011) and to decrease risk in others (Bond et al 1998; Tan et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…6 OPRM1 has been the subject of intense interest, particularly the common missense single nucleotide polymorphism (SNP) rs1799971, but also non-coding variation, with dozens of candidate gene association studies having examined a wide range of phenotypes. 1214 Many of the initial claims about associations between the candidate missense variant rs1799971 and clinical phenotypes have not proven to be robust, 15, 16 although modest effects do appear to be present. 17, 18 In addition to OPRM1, studies have also examined the relationship between methadone metabolism and candidate polymorphisms in genes encoding cytochrome P450 enzymes, including CYP3A4, CYP2B6 and CYP2D6 .…”
Section: Introductionmentioning
confidence: 99%